Let-7b Regulates Myoblast Proliferation by Inhibiting IGF2BP3 Expression in Dwarf and Normal Chicken - Lin, Shumao; Luo, Wen; Ye, Yaqiong; Bekele, Endashaw J.; Nie, Qinghua; Li, Yugu; Zhang, Xiquan (Frontiers in Physiology, 2017)
The sex-linked dwarf chicken is caused by the mutation of growth hormone receptor (GHR) gene and characterized by shorter shanks, lower body weight, smaller muscle fiber diameter and fewer muscle fiber number. However, the precise regulatory pathways that lead to the inhibition of skeletal muscle growth in dwarf chickens still remain unclear. Here we found a let-7b mediated pathway might play important role in the regulation of dwarf chicken skeletal muscle growth. Let-7b has higher expression in the skeletal muscle of dwarf chicken than in normal chicken, and the expression of insulin-like growth factor 2 mRNA binding protein 3 (IGF2BP3), which is a translational activator of IGF2, showed opposite expression trend to let-7b. In vitro cellular assays validated that let-7b directly inhibits IGF2BP3 expression through binding to its 3’UTR region, and the protein level but not mRNA level of IGF2 would be reduced in let-7b overexpressed chicken myoblast. Let-7b can inhibit cell proliferation and induce cell cycle arrest in chicken myoblast through let-7b-IGF2BP3-IGF2 signaling pathway. Additionally, let-7b can also regulate skeletal muscle growth through let-7b-GHR-GHR downstream genes pathway, but this pathway is non-existent in dwarf chicken because of the deletion mutation of GHR 3’UTR. Notably, as the loss binding site of GHR for let-7b, let-7b has enhanced its binding and inhibition on IGF2BP3 in dwarf myoblast, suggesting that the miRNA can balance its inhibiting effect through dynamic regulate its binding to target genes. Collectively, these results not only indicate that let-7b can inhibit skeletal muscle growth through let-7b-IGF2BP3-IGF2 signaling pathway, but also show that let-7b regulates myoblast proliferation by inhibiting IGF2BP3 expression in dwarf and normal chickens.